The multigap resistive plate chamber as time-of-flight detector for the STAR experiment at RHIC - Lamas V., José (2002)
The Multigap Resístive Plate Chamber (MRPC) is a suítable candidate for the Time-of-Flight system for the STAR experiment at RHIC at the BNL A time resolution of 50 ps with an efficiency of 98 %has been measured with MRPCs composed of 6 gas gaps of 220 ¡.tm. Results obtained during the year 2000 are reported here. © 2002 CSI. All rights reserved